Theoretical study on functionalized acrylonitrile compounds with a large second-order nonlinear optical response. (9th November 2020) - Gong, Lijing; Ma, Cheng; Liu, Tiejun; Lv, Jinkai; Xun, Xianchao
Abstract : The nonlinear optical properties of the studied compounds were studied with the help of DFT calculations. Abstract : The discovery and design of new materials with superior second-order nonlinear optics (NLO) performance is a hot subject of research in the fields of organic chemistry and materials science. Currently, density functional theory (DFT) is a powerful tool for interpreting experimental observations and designing novel materials with desired properties. In this work, based on the reported functionalized acrylonitriles, we have designed another two compounds by the introduction of acceptor moieties. The geometrical/electronic structures, electronic transition and second-order NLO properties of the designed compounds and the two reported compounds are systematically investigated by utilizing DFT and TD–DFT methods. The investigation shows that the different substituents have a greater effect on the distribution of FMOs, energy gap, electronic absorption and the second-order NLO properties. In addition, the second-order NLO response can be further enhanced by increasing the electron-accepting ability of the substituent. These studied compounds were found to have great NLO properties, indicating that the second-order NLO response can be effectively modulated by the introduction of donor or acceptor groups. Considering their strong NLO response, the studied compounds have potential to be used as excellent second-order NLO materials.